Protein and peptide-based microarrays for multiplex detection - Rabiee, Navid; Hamblin, Michael R. (IOP ebooks. 2020 collection., 2020)
This book discusses the aspects of protein and peptide-based microarrays for multiplex detection, based on Rabiee's Theory. It provides a thorough introduction to the field, before examining protein and peptide-based microarrays in greater detail, along with their related problems and solutions. Also covered are the materials and fabrication methods involved with protein microarrays. It offers an outlook on the future of the field within its conclusion and provides an understanding of cutting-edge aspects and horizons of this topic and is an excellent guide for scientists, students and doctors.